BJ-B11, an Hsp90 Inhibitor, Constrains the Proliferation and Invasion of Breast Cancer Cells - Liu, Kaisheng; Chen, Juan; Yang, Fang; Zhou, Zhifan; Liu, Ying; Guo, Yaomin; Hu, Hong; Gao, Hengyuan; Li, Haili; Zhou, Wenbin; Qin, Bo; Wang, Yifei (Frontiers in Oncology, 2019)
Breast cancer is the most frequently diagnosed non-skin cancer and the leading cause of cancer-related deaths in women; however, its underlying etiology remains largely unknown. In this study, we systematically analyzed breast cancer tissues using comprehensive iTRAQ labeled quantitative proteomics, identifying 841 differentially expressed proteins (474 and 367 significantly over- and under-expressed, respectively), which were annotated by protein domain analysis. All the heat shock proteins identified were upregulated in breast cancer tissues; Hsp90 upregulation was also validated by RT-qPCR and immunohistochemistry, and high Hsp90 protein levels correlated with poorer survival. Hsp90AA1 overexpression promoted MDA-MB-231 cell proliferation, whilst BJ-B11, an Hsp90 inhibitor, hampered their invasion, migration, and proliferation in a time and dose-dependent manner and induced cell cycle arrest and apoptosis. BJ-B11 inhibited the expression of epithelial-mesenchymal transition (EMT) marker in MDA-MB-231 cells, whereas Hsp90AA1 promoted its expression. Moreover, BJ-B11 inhibited tumor growth in xenograft model. Altogether, Hsp90 activation is a risk factor in breast cancer patients, and BJ-B11 could be used to treat breast cancer.